Cognitive therapy for internalised stigma in people experiencing psychosis: A pilot randomised controlled trial. (30th June 2016) - Morrison, Anthony P.; Burke, Eilish; Murphy, Elizabeth; Pyle, Melissa; Bowe, Samantha; Varese, Filippo; Dunn, Graham; Chapman, Nicola; Hutton, Paul; Welford, Mary; Wood, Lisa J.
Abstract: We aimed to evaluate the feasibility of Cognitive Therapy (CT) as an intervention for internalised stigma in people with psychosis. We conducted a single-blind randomised controlled pilot trial comparing CT plus treatment as usual (TAU) with TAU only. Participants were assessed at end of treatment (4 months) and follow-up (7 months). Twenty-nine participants with schizophrenia spectrum disorders were randomised. CT incorporated up to 12 sessions over 4 months (mean sessions=9.3). Primary outcome was the Internalised Stigma of Mental Illness Scale – Revised (ISMI-R) total score, which provides a continuous measure of internalised stigma associated with mental health problems. Secondary outcomes included self-rated recovery, internalised shame, emotional problems, hopelessness and self-esteem. Recruitment rates and retention for this trial were good. Changes in outcomes were analysed following the intention-to-treat principle, using ANCOVAs adjusted for baseline symptoms. There was no effect on our primary outcome, with a sizable reduction observed in both groups, but several secondary outcomes were significantly improved in the group assigned to CT, in comparison with TAU, including internalised shame, hopelessness and self-rated recovery. Stigma-focused CT appears feasible and acceptable in people with psychosis who have high levels of internalised stigma. A larger, definitive trial is required. Highlights: Stigma-focused CT is feasible and acceptable in people experiencing psychosis who have internalised stigma. CT showed promise for reducing internalised shame and hopelessness and improving self-rated recovery. A definitive, appropriately powered trial is required and appears both feasible and deliverable.